2023
DOI: 10.1097/phh.0000000000001726
|View full text |Cite
|
Sign up to set email alerts
|

Rural Public Health Data Challenges During the COVID-19 Pandemic: The Case for Building Better Systems Ahead of a Public Health Crisis

Abstract: Context: Rural public health personnel serve communities that have been particularly susceptible to COVID-19 and yet faced the pandemic with far less well-resourced capacity than their urban counterparts. A critical aspect of addressing local health inequities is access to high-quality population data and the capacity to effectively use data to support decision making. However, much of the data required to investigate inequities are not readily available to rural local health departments and the tools and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Issues related to obtaining quality public health data are well documented in the literature and include the critical problems of a lack of investment in public health data systems and infrastructure [ 36 - 39 ], issues with data quality [ 40 - 42 ] and data fragmentation [ 43 , 44 ], and the sparse data available about rural communities [ 8 , 45 ]. While every effort was made to include as much timely and comprehensive data as possible in SHAREdash, these larger data problems clearly impacted the usability of this tool.…”
Section: Discussionmentioning
confidence: 99%
“…Issues related to obtaining quality public health data are well documented in the literature and include the critical problems of a lack of investment in public health data systems and infrastructure [ 36 - 39 ], issues with data quality [ 40 - 42 ] and data fragmentation [ 43 , 44 ], and the sparse data available about rural communities [ 8 , 45 ]. While every effort was made to include as much timely and comprehensive data as possible in SHAREdash, these larger data problems clearly impacted the usability of this tool.…”
Section: Discussionmentioning
confidence: 99%
“…Limited capacity LHDs access data to quickly disseminate analyses externally, and data platforms help fill the gaps that exist due to their lack of access to staffing and expertise. This aligns with research that found limited capacity LHDs “need data that are easy to manage, understand, and communicate with.”3 (p6) Therefore, data should be analyzed and predigested into stories—ready for immediate use. Support in accessing data should center strategies for immediate application, including how to simply describe data limitations—a finding similar to that of other studies 3,7.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with research that found limited capacity LHDs “need data that are easy to manage, understand, and communicate with.”3 (p6) Therefore, data should be analyzed and predigested into stories—ready for immediate use. Support in accessing data should center strategies for immediate application, including how to simply describe data limitations—a finding similar to that of other studies 3,7. Moderate capacity LHDs use data to serve intermediate-term goals via benchmarking and resource deployment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations